Fashion and beauty advertising models’ age and its impact on over 50 female consumers’ purchase intention - Pinho, Maria Joana Magalhães de (2013)
The dissertation that is now presented, aims to study a social phenomenon that has gained increasing importance and study it under a commercial perspective, concluding about the impacts that it can bring for some markets. The purpose is to study the impact of the Fashion and Beauty advertisements models’ age on the purchase intention of female consumers over 50. This is a segment that has been gaining weight, expression and importance, and it is crucial to understand if it is been addressed with an effective communication strategy. This research, after identifying some gaps in the literature on this such contemporaneous topic, extracted those that seem to be the most important variables to develop a study and draw conclusions through statistical analysis and validation, about how women over 50 have been seeing the markets communication, and how it impacts on the purchase intention. In the first part of the study a deep review of the literature is made, providing a structured knowledge of what has already been studied by other authors on this topic, and on other matters related to or involved with this issue. In the second stage, the approach is quantitative. In the presented study 259 people were involved and asked to answer to a series of questions on the topics described above and according to their opinions and feelings towards some advertising images exhibited throughout the questionnaire. The results revealed that although some values are low to be considered significant almost all the relationships between the variables, suggested by the literature, have occurred. The results are very interesting and highly applicable outputs to the markets concerned. All findings related to this study are adequately summarized in Section 6.